Review of Dactylosternum Wollaston, 1854 from China and Japan (Coleoptera, Hydrophilidae, Sphaeridiinae) - Mai, Zuqi; Hu, Jian; Minoshima, Yûsuke N.; Jia, Fenglong; Fikáček, Martin (Zootaxa, 2022)
The species of the genus Dactylosternum Wollaston, 1854 occurring in China and Japan are reviewed. Ten species are recognized to occur in China, two of which were also recorded from Japan. Four new species are described from China: Dactylosternum nanlingensis Mai et Jia, sp. nov. (Guangdong, Jiangxi) from fungal hyphae on fallen wood, D. songxiaobini Mai et Jia, sp. nov. (Guangxi) from fallen wood with termites, D. pseudolatum Mai et Jia, sp. nov. (Guangdong, Hubei, Hunan, Jiangxi, Fujian, Hainan, Yunnan) and D. frater Mai et Jia, sp. nov. (Yunnan) from banana trees. Dactylosternum latum (Sharp, 1873) and D. salvazai Orchymont, 1925 are reported for the first time from China, and species recorded previously (D. abdominale (Fabricius, 1792), D. corbetti Balfour-Browne, 1942, D. hydrophiloides (MacLeay, 1825) and D. pui Jia, 2002) are redescribed or diagnosed. Dactylosternum abdominale (Fabricius, 1792) is confirmed to occur in Japan. Dactylosternum latum is only known from Japan based on type specimens believed to be collected in Nagasaki by G. Lewis in late 19th century; since the species was never re-collected in Japan later, its distribution in Japan seems doubtful. Dactylosternum vitalisi Orchymont, 1925 is synonymized with D. latum (Sharp, 1873), the variability of the latter species is discussed. We moreover found that the type series of D. vitalisi contains two species, with some paratypes actually belonging to D. pseudolatum Mai et Jia, sp. nov. All species of Dactylosternum living in China and Japan are diagnosed and illustrated and a key allowing their identification is provided. We infer that the compact antennal club and paralleled body form are characters related to the life inside of plant tissues, while loose antennal club and rounded body form is present in free living Dactylosternum species. The combination of characters for distinguishing Dactylosternum from other genera of Coelostomatini is also provided.